RETRACTED: Assesment of local water resource in Kuljuktov mountain system - Halimova Gulshan; Qalandarova Dilobar; Anvarova Zebo (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001